Maternal and Fetal Outcome in Cardiac Patients a Cross-Sectional Study at Tertiary Care Setting - Zareena Begum, Asma Ghani, Ahmad Fawad, Hafiza Nida Mumtaz, Shazia Firdos Chohan, Naureen Ghani, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In low-resource settings, when specialist treatment is unavailable, cardiovascular disease during pregnancy presents severe hazards to the health of both the mother and the fetus. Objective: To assess maternal and fetal outcomes in pregnant women with cardiac disease admitted to a tertiary care hospital, identifying common cardiac conditions, associated complications, and predictors of adverse outcomes. Methodology: This cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Saidu Group of Teaching Hospitals, Swat and North West General Hospital, Peshawar over one year (June, 2022 to May 2023). In all, 164 pregnant women who had a history of heart problems were considered. Information on the patient's demographics, heart condition (type and severity), pregnancy, challenges throughout pregnancy, foetal outcomes, and neonatal health were culled from clinical records. Data was summarized using descriptive statistics, and relationships between maternal cardiac problems and fetal outcomes were analyzed using t-tests, with a p-value less than 0.05 being deemed statistically significant. Results: Out of all cardiac conditions, rheumatic heart disease accounted for 37.80% of cases, congenital heart disease for 29.27%, cardiomyopathies for 19.51%, and ischemic heart disease for 13.41%. Heart failure (25.61%), arrhythmias (21.95%), thromboembolic events (10.98%), and pulmonary edema (12.20%) were among the maternal problems that contributed to the 4.88% maternal death rate. Preterm delivery (45.12%), intrauterine growth restriction (23.17%), and stillbirth (8.54%) were all notable fetal problems; 25.61% of these babies needed to be admitted to the neonatal intensive care unit (NICU). The rates of preterm delivery (53.13%, p = 0.03), NICU hospitalizations (34.38%, p = 0.02), and stillbirth (15.63%, p = 0.01) were greatest among cardiomyopathies, indicating a substantial connection between the severity of the maternal condition and bad newborn outcomes. Conclusion: Early risk assessment and multidisciplinary care are necessary to enhance maternal and newborn outcomes when maternal heart illness is present, since it is linked with major pregnancy problems. Keywords: Maternal cardiac disease, pregnancy outcomes, rheumatic heart disease, congenital heart disease.